Dehumidification Classification and Advanced Research in Deep Dehumidification Technology - Zeng Ruixuan; Yan Chengchu; Li Mei (Zhileng xuebao)
At present, different fields have different requirements for humidity. The industry does not have a unified standard for the division of dehumidification levels, which is likely to cause confusion and inconvenience when multiple fields are crossed. To solve the above-mentioned problems, this study analyzes the existing dehumidification technology. It introduces the dehumidification requirements of comfort air conditioning, equipment air, industrial production, and other fields. The dehumidification level is uniformly divided. After dehumidification treatment, a dew point >?20 ℃ is considered as shallow dehumidification, a dew point between ?20 ℃ and ?65 ℃ is considered as deep dehumidification, and a dew point 65 ℃ is considered as extremely deep dehumidification. The latest research progress in deep dehumidification technology can be summarized as follows: for freezing dehumidification, direct evaporative refrigeration and pressurized freezing dehumidification can reduce the dew point of the outlet air to less than ?10 ℃ to ?20 ℃; for solution dehumidification, the dew point of the outlet air can reach ?10 ℃ to ?20 ℃, or even lower, by cooling the dehumidifying liquid or compressing the humid air.